Peningkatan Proses dan Hasil Belajar Matematika Menggunakan Model Quantum Teaching Berbantu Media Audio Visual: Penelitian - Huswatul Hasanah; Nurlev Avana; Opi Andriani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe the improvement of the learning process and mathematics learning outcomes of third-grade students at SD Negeri 04/II Jaya Setia through the application of the Quantum Teaching model assisted by audio-visual media. This research was motivated by the low mathematics achievement, where only 35% of students reached the Minimum Mastery Criteria (KKTP) with a score of 70, while 65% had not yet achieved it. The research employed Classroom Action Research (CAR), conducted in two cycles consisting of planning, implementation, observation, and reflection. Data were collected through observation, tests, and documentation, with instruments including teacher and student observation sheets, test items, and learning documentation. The results showed that the implementation of the Quantum Teaching model assisted by audio-visual media improved both student learning activities and outcomes. In Cycle I, the average score reached only 74.1% with 60% classical mastery, while in Cycle II the average increased to 89.6% with 90% classical mastery. In addition, the observation results revealed an improvement in the teaching and learning process, where teacher performance increased from 80% in Cycle I to 84.5% in Cycle II, and student participation increased from 79.15% in Cycle I to 85.25% in Cycle II.